Chitosan-Magnetite Nanocomposite as a Sensing Platform to Bendiocarb Determination - Casagrande-Denardin, J; Melo-Freire, R (Springer Verlag, 2018)
A novel platform for carbamate-based pesticide quantification using a chitosan/magnetic iron oxide (Chit-Fe3O4) nanocomposite as a glassy carbon electrode (GCE) modifier is shown for an analytical methodology for determination of bendiocarb (BND). The BND oxidation signal using GCE/Chit-Fe3O4 compared with bare GCE was catalyzed, showing a 37.5% of current increase with the peak potential towards less positive values, showing method’s increased sensitivity and selectivity. Using square-wave voltammetry (SWV), calibration curves for BND determination were obtained (n = 3), and calculated detection and quantification limits values were 2.09 × 10−6 mol L−1 (466.99 ppb) and 6.97 × 10−6 mol L−1 (1555.91 ppb), respectively. The proposed electroanalytical methodology was successfully applied for BND quantification in natural raw waters without any sample pretreatment, proving that the GCE/Chit-Fe3O4 modified electrode showed great potential for BND determination in complex samples. [Figure not available: see fulltext.]. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Bendiocarb; Magnetic nanoparticles; Nanocomposite; Chitosan; Electrochemical sensor